Identification E-SIM for Motorcycle Security Using Atmega 8 Microcontroller - Saiyar, Hafdiarsya; Desmulyati, Desmulyati (Jurnal Riset Informatika, 2022)
Motorcycle theft is getting more disturbing, so it encourages the author to make security devices on motorbikes. This study has created a security system that can secure motorcycles using an e-SIM based on the Atmega-8 Microcontroller. Where the e-SIM has a chip, the chip itself has 7 bytes. In this case, the authors take advantage of the 7-byte chip in the e-SIM. The e-SIM will replace the motorcycle ignition key. Not only that, but the e-SIM will also give orders to the motor starter to start the motorcycle. Thus, only the owner of the e-SIM who already has a sim can give the motorcycle ON and OFF orders. The research method used is direct observation of the selected object, namely the author's home environment, and conducting literature studies related to the Atmega-8 microcontroller. This study aims to create a security system for motorcycle vehicles to avoid theft and the use of motorcycles for children without driving licenses.